THE RELATIONSHIP AMONG METACOGNITIVE AWARENESS, MOTIVATION, AND LISTENING ACHIEVEMENT - Clementin Kortisarom (Widya Mandala Surabaya Catholic University, 2020)
This research was conducted to investigate the possible relationship among EFL students’ metacognitive awareness, motivation, and achievement with the context of independent learning carrying out Listening activity. Twenty-nine third-semester students of English Department at one Catholic university in Surabaya were asked to be the participants. A metacognitive-awareness questionnaire was distributed as well as the motivation questionnaire. Besides, a listening comprehension test taken from students’ independent learning module was used to obtain the students’ listening achievement. Then, the quantitative data was analyzed using Pearson’s correlation coefficient. The result of this study shows the facts that both oppose and approve the related theory.